Control of feed intake in ruminants continuous rumen infusion studies (Project 802) - J.C. Parks; K.S. Lusby; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1971)
Since the requirement of animals for net energy for maintenance (NEm) is influenced largely by weight of the animal, feed efficiency and animal performance improve rapidly as feed intake surpasses maintenance requirements. Once that constant "overhead" is satisfied, remaining nutrients are available for growth and production. The object of the study reported here was to see if ruminants are capable of digesting and metabolizing nutrient intakes in excess of what they normally consume. Fistulated sheet were the experimental animals. The basal diet is shown in Table 3. The ingredients were suspended in water, filtered through cheesecloth, held in suspension by continuous agitation, and continuously metered with a peristaltic infusion pump into the rumen, (through the rumen fistula). Continuous infusion was to remove the effect of "meal" eating and to establish constant conditions in the rumen. Animals were adapted to an all-concentrate ration before being switched to the liquid diet.
Keywords: Cattlemen' s Day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station); 546; Beef; Feed intake; Rumen; Energy maintenance